Respiratory syncytial virus hospitalisation trends in children with haemodynamically significant heart disease, 1997–2012. (10th May 2016) - Chu, Patricia Y.; Hornik, Christoph P.; Li, Jennifer S.; Campbell, Michael J.; Hill, Kevin D.
Abstract: Objective: The aim of the study was to evaluate the trends in respiratory syncytial virus-related hospitalisations and associated outcomes in children with haemodynamically significant heart disease in the United States of America. Study design: The Kids' Inpatient Databases (1997–2012) were used to estimate the incidence of respiratory syncytial virus hospitalisation among children ⩽24 months with or without haemodynamically significant heart disease. Weighted multivariable logistic regression and chi-square tests were used to evaluate the trends over time and factors associated with hospitalisation, comparing eras before and after publication of the 2003 American Academy of Pediatrics palivizumab immunoprophylaxis guidelines. Secondary outcomes included in-hospital mortality, morbidity, length of stay, and cost. Results: Overall, 549, 265 respiratory syncytial virus-related hospitalisations were evaluated, including 2518 (0.5%) in children with haemodynamically significant heart disease. The incidence of respiratory syncytial virus hospitalisation in children with haemodynamically significant heart disease decreased by 36% when comparing pre- and post-palivizumab guideline eras versus an 8% decline in children without haemodynamically significant heart disease (p<0.001). Children with haemodynamically significant heart disease had higher rates of respiratory syncytial virus-associated mortality (4.9 versus 0.1%, p<0.001) and morbidity (31.5 versus 3.5%, p<0.001) and longer hospital length of stay (17.9 versus 3.9 days, p<0.001) compared with children without haemodynamically significant heart disease. The mean cost of respiratory syncytial virus hospitalisation in 2009 was $58, 166 (95% CI:$46, 017, $70, 315). Conclusions: These data provide stakeholders with a means to evaluate the cost–utility of various immunoprophylaxis strategies.